ANALISIS HASIL PEMBUATAN PETA KONTUR DENGAN METODE POLIGON TERTUTUP MENGGUNAKAN PROGRAM SURFER 15 DI AREA GEDUNG DIREKTORAT POLITEKNIK NEGERI SEMARANG (AREA GEDUNG DIREKTORAT - PKM - GEDUNG SC - GEDUNG KERJA SAMA POLITEKNIK NEGERI SEMARANG): ANALISIS HASIL PEMBUATAN PETA KONTUR DENGAN METODE POLIGON TERTUTUP MENGGUNAKAN PROGRAM SURFER 15 DI AREA GEDUNG DIREKTORAT POLITEKNIK NEGERI SEMARANG (AREA GEDUNG DIREKTORAT - PKM - GEDUNG SC - GEDUNG KERJA SAMA POLITEKNIK NEGERI SEMARANG) - Edo Wiguna; Roselina Rahmawati; Muhammad Mukhlisin; Leily Fatmawati; Teguh Mulyo Wicaksono; Lely Angraeni Wijaya; Dianita Ratna Kusumastuti; Risman (Bangun Rekaprima, 2026)
This study aims to analyze the results of contour map creation using the closed polygon method through the Surfer 15 program in the area of ​​the Semarang State Polytechnic Directorate Building, which includes the area of ​​the Directorate Building - PKM - SC Building - Cooperation Building. Contour map creation was carried out to determine the topographic conditions and characteristics of the land slope in the area, which affect the planning and development of campus infrastructure. The methods used in this study include collecting coordinate and elevation data in the field, data processing using the closed polygon method to obtain high accuracy in positioning, and land surface modeling with Surfer 15 software. The results of data processing are presented in the form of contour maps and cross-sections and longitudinal sections, which are then analyzed to determine the level of land slope in each measurement segment. From the analysis results, it was found that the topography in the section of the Directorate Building - PKM - SC Building - Cooperation Building showed significant variations in height. Based on the measurement results, the slope of the land in the cross section A–A (Directorate–PKM) is 5.12%, section B–B (Directorate–PKM) is 3.59%, section C–C (Directorate–SC Building) is 7.94%, and the longitudinal section of the Tennis Court–Workshop Building has a slope of 2.44%. These values ​​indicate that the research area has varying elevation differences, with a tendency of gentle to moderate slopes. Overall, the results of this study indicate that the closed polygon method and modeling with Surfer 15 are able to provide an accurate and detailed topographical picture of the land conditions in the Semarang State Polytechnic environment. This land slope information can be used to support spatial planning, drainage, and the development of more efficient and sustainable campus facilities.